2020
DOI: 10.1299/jamdsm.2020jamdsm0027
|View full text |Cite
|
Sign up to set email alerts
|

Internet of things and simulation approach for decision support system in lean manufacturing

Abstract: Today, Industry 4.0 concerns a rapid advancement in manufacturing technologies which help industries increase their productivity. To adopt Industry 4.0 concept is still visionary by certain lean manufacturers when the communication technologies interfaces are not fully equipped at the production system. Most of the facilities towards digitalization are also expensive and require many specialists in different fields to manage the technologies. Therefore, most data analytics (DA) engineering is cannot be employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…In particular, the findings of this study agree with previous research on the use of DS in support of LP practices that considered the 'production planning and control' LP bundle (e.g. Stojanovic et al 2016;Deuse et al 2018;Kutschenreiter-Praszkiewicz 2018;Mayr et al 2018;Abd Rahman et al 2020;Ito et al 2020;Sarkar et al 2020;Shahin et al 2020;Valamede and Akkari 2020). However, differently from previous research, the results of this research demonstrate also that the application of the identified set of techniques and tools is not limited to the 'production planning and control' bundle but can potentially support all the LP bundles.…”
Section: Answering Rq1: What Ds Techniques and Tools Can Support Lp P...supporting
confidence: 86%
See 1 more Smart Citation
“…In particular, the findings of this study agree with previous research on the use of DS in support of LP practices that considered the 'production planning and control' LP bundle (e.g. Stojanovic et al 2016;Deuse et al 2018;Kutschenreiter-Praszkiewicz 2018;Mayr et al 2018;Abd Rahman et al 2020;Ito et al 2020;Sarkar et al 2020;Shahin et al 2020;Valamede and Akkari 2020). However, differently from previous research, the results of this research demonstrate also that the application of the identified set of techniques and tools is not limited to the 'production planning and control' bundle but can potentially support all the LP bundles.…”
Section: Answering Rq1: What Ds Techniques and Tools Can Support Lp P...supporting
confidence: 86%
“…A narrow range of studies proposed or presented practical applications of DS to specific LP practices. Ito et al (2020) adopt simulation as a data analytics tool applied to field data in a real-time Andon system, supporting 'visual management of production control'. Abd apply simulation as a data analytics tool to generate overall equipment effectiveness (OEE) values as the 'feedback on performance metrics practice' of a production line.…”
Section: Linking Data Science and Lean Productionmentioning
confidence: 99%
“…IoT (Internet of Things) technologies such as RFID (Radio Frequency Identification) and LPWAN (Low Power Wide Area Network) are utilised to enhance digital traceability and to provide real-time information which can be effectively applied in Lean Manufacturing to identify and eliminate the waste [10][11]. IoT has also been used in integrating machines in the shop floor and also to connect to the machines with Andon systems to enhance the decision support system for process improvement [12][13]. IoT has also been applied to transform the traditional JIT (Just-In-Time) into dynamic JIT, which successfully addresses the challenges of traditional JIT by integrating modules integrated with IoT technologies into the Manufacturing Execution System (MES) [14].…”
Section: Industry 40 Tools Supporting Lean Manufacturingmentioning
confidence: 99%
“…Malik and Bilberg proposed a method for assigning tasks to robots or people in Human-Robot Collaborative (HRC) assembly, based on the physical properties of the components, HRC safety, and the dynamics of the HRC environment such as part presentation and feeding [184]. The IoT and simulation could be used to support expert-less decision making, in a similar way to the classic Andon tool does [185]. In any case, systems integration will be needed to ensure that Lean manufacturing systems meet the Industry 4.0 requirements [186].…”
Section: Lean Tools For the Industry 40 Eramentioning
confidence: 99%